Medical and Psychological Rehabilitation Program for Anxiety and Depressive Post-COVID Disorders in Remote Interaction Conditions - Burdeinyi, Андрій (Psychosomatic Medicine and General Practice, 2024)
Relevance. The COVID-19 pandemic and its consequences continue to pose a serious challenge to the healthcare system both in Ukraine and globally. After a SARS-CoV-2 infection, many patients develop post-COVID syndrome, which may include affective disorders, cognitive impairments, and other symptoms. This condition negatively impacts the quality of life and the effectiveness of treatment for anxiety and depressive disorders. The mental health consequences are especially relevant for individuals in conflict zones, where the incidence of anxiety and depressive disorders is increasing. Remote interaction opens new possibilities for providing medical and psychological rehabilitation, enabling access to care when in-person consultations are limited. A key component of this approach is the proactive model of psychosomatic medicine, which focuses not only on responding to symptoms but also on preventing their development and maintaining the patient's overall health. In the context of remote interaction, such a model allows for continuous monitoring of patients' conditions and actively engaging them in the treatment process, which is particularly important for individuals experiencing the effects of post-COVID syndrome or war. Objective. To analyze the effectiveness of the medical and psychological rehabilitation program for anxiety and depressive post-COVID disorders in remote interaction conditions through a parallel randomized non-blinded controlled trial with two groups, where the control group received standard treatment. Methods. The study sample consisted of 240 individuals with anxiety and depressive post-COVID disorders, which complied with ethical and deontological norms according to the principles outlined in the Helsinki Declaration. The tools used in the study included the Patient Health Questionnaire-9 (PHQ-9) and the Generalized Anxiety Disorder-7 (GAD-7) scale. Results. At the beginning of the study, the mean PHQ-9 scores in the study group and the control group were almost identical (16.590±6.612 and 16.127±6.811, respectively) (p=0.594; t=-0.534). However, by day 63, participants in the study group showed a significant reduction in the mean depression score to 6.942±5.073, while the control group's score remained nearly unchanged at 15.567±6.540 (p<0.001; t=11.437). At the start of the study, the mean anxiety symptoms according to the GAD-7 in the study group (14.926±4.108) and the control group (14.644±4.137) (p=0.597; t=-0.530) were also nearly identical. By day 63, the mean anxiety score in the study group had significantly decreased to 3.991±3.589, while it remained significantly higher in the control group at 12.966±3.980 (p<0.001; t=18.355). Conclusions. The study results show a significant improvement in the mental health of participants in the study group after 63 days of the medical and psychological rehabilitation program in remote interaction conditions. At the beginning of the study, the levels of depression and anxiety symptoms in the study and control groups were almost identical, indicating homogeneity between the groups in terms of initial mental health status. However, after the intervention, there was a significant reduction in depression and anxiety levels in the study group compared to the control group. These results indicate the effectiveness of the medical and psychological rehabilitation program in remote interaction conditions in reducing symptoms of depression and anxiety in cases of anxiety and depressive post-COVID disorders. Key words: Post-COVID syndrome, anxiety, depression, proactive psychosomatic medicine, telemedicine, telepsychology